Design and Evaluation of Mixed Reality-Based Mobile English Instruction: A Comparative Analysis of Learning Outcomes - Fang, Lanlan; Wang, Xiujuan; Zhang, Liang (International Journal of Interactive Mobile Technologies (iJIM), 2026)
With the deep integration of educational technology and second language acquisition (SLA), mixed reality (MR) technology—combining the immersive qualities of virtual reality (VR) and the contextual relevance of augmented reality (AR)—has provided a novel pathway to address key challenges in traditional mobile English learning, including limited immersion, insufficient interaction, and the disconnection between knowledge and real-world application. This study aims to construct multiple differentiated MR-based mobile English instructional designs and to systematically compare their learning effects across four dimensions: knowledge acquisition, language proficiency, learning engagement, and cognitive load. A quasi-experimental design was employed, in which participants were randomly assigned to one of four groups: a context-immersive MR group, a collaborative inquiry MR group, a personalized adaptive MR group, and a traditional mobile learning control group. An eight-week instructional intervention was implemented. The expected findings indicate that (a) all three MR-based instructional designs perform significantly better than the traditional mobile learning model in vocabulary retention, listening and speaking proficiency, and learning engagement; (b) the context-immersive MR group demonstrates superior performance in contextualized language use and cultural awareness; (c) the collaborative inquiry MR group exhibits distinct advantages in cooperative communication and problem-solving skills; and (d) the personalized adaptive MR group experiences the lowest cognitive load and the highest satisfaction across learners of different proficiency levels. This study contributes to the theoretical development of technology-enhanced SLA, provides empirical support for optimizing MR-based mobile English instructional design, and offers practical guidance for the deeper integration of MR technology into second language education.